2016
DOI: 10.1016/j.ymeth.2016.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome guided identification of novel functions of RECQ1 helicase

Abstract: Gene expression changes in the functional absence of a specific RecQ protein, and how that relates to disease outcomes including cancer predisposition and premature aging in RecQ helicase associated syndromes, are poorly understood. Here we describe detailed experimental strategy for identification of RECQ1-regulated transcriptome that led us to uncover a novel association of RECQ1 in regulation of cancer cell migration and invasion. We initiated a focused study to determine whether RECQ1, the most abundant Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…A novel observation in the current study is that low RECQL1 also influenced survival in ER+ cohorts that received endocrine therapy implying that RECQL1 could also have predictive significance. Given the recent evidence that RECQL1 may modulate gene expression (26, 28), we speculate that ER and/or ER mediated gene expression could be influenced by low RECQL1 in tumours. To explore this hypothesis we investigated ERα protein levels in control and RECQL1-depleted breast cancer cells.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A novel observation in the current study is that low RECQL1 also influenced survival in ER+ cohorts that received endocrine therapy implying that RECQL1 could also have predictive significance. Given the recent evidence that RECQL1 may modulate gene expression (26, 28), we speculate that ER and/or ER mediated gene expression could be influenced by low RECQL1 in tumours. To explore this hypothesis we investigated ERα protein levels in control and RECQL1-depleted breast cancer cells.…”
Section: Discussionmentioning
confidence: 91%
“…Given the recent evidence that RECQL1 may modulate gene expression (26, 28), we conducted preliminary studies to explore if RECQL1 may impact upon ERα expression in breast cancer cell lines. In control cells, as expected, ERα expression was not detectable in MDA-MB-468 cells and MCF-7 cells have proficient ERα expression.…”
Section: Resultsmentioning
confidence: 99%
“…In the future, it will be important to assess RECQL1’s role in modulating gene expression in cancer cells exposed to agents that induce DNA damage, particularly oxidative stress given the observations that RECQL1 deficiency sensitizes cells to ionizing radiation or H 2 O 2 . Co-regulation of gene expression by RECQL1 and the sequence-related WRN and BLM helicases suggests that the potentially overlapping roles of human RecQ helicases in gene expression [95] may contribute to the complexity of the DNA damage response.…”
Section: Human Recq Helicases and Their Roles In Response To Nuclear mentioning
confidence: 99%
“…WRN is also likely to regulate expression of genes with enriched G4 motifs at these locations, only in a different set compared with BLM, suggesting distinct roles of the two RecQ helicases in disease pathogenesis [156]. Other studies that included chromatin immunoprecipitation experiments suggested that RECQL1 [157], XPB, and the Fe–S helicase XPD [147] regulate gene expression directly through their interactions with predicted G4-forming sequences in promoters. Certain RecQ and Fe–S helicases also preferentially interact with and resolve unusual DNA structures in the G-rich telomeric repeats (see Telomeres ) (Figure 2).…”
Section: Biochemistrymentioning
confidence: 99%